Model Geohidrologi paska Tambang daerah penambangan Batubara Kec. Tabang Kab. Kutai Kartanegara (Jurnal Geologi Pertambangan (JGP), 2023)
AbstrakCoal mining is a commodity that attracts many investors, with a large number of or abundant reserves in the area, so coal mining activities are very rife in the subdistrict Tabang, Regency Kutai Kartanegara, so that it will have both positive and negative impacts, positive impacts will certainly cause changes to improve socio-economic life, while negative impacts will cause problems related to the decrease in the quality and quantity of surface water and groundwater. The opening of land due to mining will greatly affect environmental changes such as changes in the landscape, lowering of the groundwater level, increased acidity of the soil/rock (soil becomes less fertile), chemical and physical properties, mine waste enters rivers, and causes soil damage. This condition has an impact on decreasing the quality and quantity of groundwater as a source of clean water. The purpose of this study is to determine the effect of mining on the hydrogeology of the research area, especially groundwater.Hydrogeological analysis is very important, by carrying out a Pumping Test or Slugs from 5 (five) drilling points to be carried out, so that it is expected to be able to know groundwater modeling before and after post-mining, and here you will see a comparison of groundwater flow before and after mining. . So that the hope of this research can find out and understand the hydrogeological conditions of the research area, so that it will provide information on the impact of mining activities, and it will be easier, how to overcome or control related to areas which still have potential or not, which are related to the content/potential groundwater around the mining site.Practical benefits can provide information to the public and the government about the potential content of groundwater around the research area and to know/predict the potential groundwater that can still be utilized. The stratigraphy of the study area is part of the Kutai Bacin. Lithology The formation of the study area (Balikpapan Formation) consists of alternating siltstone and claystone with sandstone with coal inserts and sandstone units. Where there are 5 (five) potential aquifers in the study area in terms of the amount/volume of groundwater, the groundwater in the study area must be monitored along with mining activities in the study area. Keywords: Modeling, groundwater, hydrogeology, post mining